Sea Ice Variability and Trends in the Western Indian Ocean Sector of Antarctica During the Past Two Centuries and Its Response to Climatic Modes. Issue 23 (6th December 2021) - Ejaz, Tariq; Rahaman, Waliur; Laluraj, C. M.; Mahalinganathan, K.; Thamban, Meloth
Abstract: Antarctic sea ice is a critical component of the ocean‐climate system. Sea ice concentration (SIC) records of various oceanic sectors of Antarctica available since 1979 reveal dramatic changes in recent years; however, there is no consensus yet on drivers of sea ice variability, changes and their future projections. The lack of long‐term SIC records has impeded the quantification of sea ice variability, trends and various forcing factors and mechanisms. Here, we present a long‐term SIC record (1809−1993 CE) for the Western Indian Ocean Sector (WIOS) of Antarctica derived from a new ice core oxygen isotope (δ 18 O) record together with three available records from Dronning Maud Land (DML), East Antarctica. This long‐term SIC record at annual resolution reveals a significant decline during 1830–1884 CE with a rate of 0.58% ± 0.12% decade −1 followed by moderate increase during 1927–1993 CE with a rate of 0.24% ± 0.11% decade −1 . Current satellite‐derived SIC records reveal an increase of 2.59 ± 0.86% decade −1 during 1994–2014 CE, which is unprecedented over the last two centuries as determined by the ice core‐derived SIC record. The satellite and ice core combined SIC record (1809−2019 CE) also reveals a significant increase in interannual variability at El Niño Southern Oscillation band and decadal variability at 16–32 years band in the last few decades. Our investigation suggests that wind‐driven sea‐ice dynamics associated with switching phases of Southern Annular Mode and remote teleconnections of Pacific oscillations largely control the interannual to decadal sea ice variability in this region. Plain Language Summary: Antarctic sea ice plays a vital role in modulating the global climate. Antarctic sea ice observation from satellites available since 1979 shows rapid changes in various oceanic sectors. However, to understand the long‐term annual sea ice variations, we have to rely on proxy records. In this study, annual sea ice concentrations (SIC) are reconstructed for the Western Indian Ocean Sector (WIOS) of Antarctica based on a new coastal ice core oxygen isotope (δ 18 O) record together with previously available records. We provide the first long‐term SIC record of the past two centuries (1809−1993 CE) at annual resolution, which shows a significant decline during 1830–1884 CE followed by a moderate increase during 1927–1993 CE. Our record (1809–1993 CE) combined with satellite record (1994–2019 CE) shows a dramatic increase in recent decades (1994–2014 CE), which is mainly influenced by the wind‐driven sea‐ice dynamics related to the positive shifting of Southern Annular Mode (SAM) and increasing El Niño Southern Oscillation (ENSO) events. Our study suggests a larger role of SAM−ENSO teleconnections in modulating interannual to decadal sea‐ice variability over the WIOS during the past two centuries. Key Points: We provide annually resolved ice core based sea ice records of two centuries (1809–1993 CE) of Western Indian Ocean sector of Antarctica Sea ice record of the past two centuries based on reconstructed and satellite records reveals unprecedented increase during 1994–2014 CE Interannual to decadal sea ice variability is controlled by Southern Annular Mode modulated wind forcing and teleconnections to Pacific oscillations